The Feed the Future Rwanda Orange- Fleshed Sweetpotato (OFSP) for Income and Nutrition Activity - International Potato Center (2016)
This three year project (2015 – 2018) aims to reach 200,000 households and 300,000 children under 5 years of age in ten districts of Rwanda, contributing to inclusive agricultural sector growth, income generation and improved nutritional status of women and children though the promotion of OFSP production and consumption. So far, 45,000 households have been reached.